2020
DOI: 10.1186/s13063-020-04277-3
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of potassium canreonate-canrenone in sinus rhythm restoration among patients with atrial fibrillation - a protocol of a pilot, randomized, double -blind, placebo-controlled study (CANREN-AF trial)

Abstract: Background: Atrial fibrillation (AF) is the most frequent cardiac arrhythmia which increases the risk of thromboembolic complications and impairs quality of life. An important part of a therapeutic approach for AF is sinus rhythm restoration. Antiarrhythmic agents used in pharmacological cardioversion have limited efficacy and potential risk of proarrhythmia. Simultaneously, underlying conditions of AF should be treated (e.g. electrolyte imbalance, increased blood pressure, neurohormonal disturbances, atrial v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The mechanisms leading to RAAS toxicity also include (i) modulation of the production of pro-inflammatory status, potentially leading to recruitment of mono/macrophages; (ii) induction of fibrosis (through AT1R); (iii) induction of vascular toxicity and modulation of angiogenesis [ 15 ]. Of note, among the RAAS-inhibiting agents, only canrenone (potassium canreonate), the active metabolite of spironolactone, can be administered intravenously [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms leading to RAAS toxicity also include (i) modulation of the production of pro-inflammatory status, potentially leading to recruitment of mono/macrophages; (ii) induction of fibrosis (through AT1R); (iii) induction of vascular toxicity and modulation of angiogenesis [ 15 ]. Of note, among the RAAS-inhibiting agents, only canrenone (potassium canreonate), the active metabolite of spironolactone, can be administered intravenously [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This favorable response may rely on the activity of canrenone that can antagonize the disequilibrium of RAAS pathway. Among the RAAS-inhibiting agents, only canrenone (potassium canreonate), the active metabolite of spironolactone, can be administered intravenously [9].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 serves a counterbalancing role in Renin-Angiotensin-Aldosterone System (RAAS), i.e. it cleaves away (i) phenylalanine from angiotensin (Ang) II, converting it to Ang-(1-7), and (ii) leucine from Ang I, converting it to Ang- (1)(2)(3)(4)(5)(6)(7)(8)(9). SARS-CoV-2 infection appears to downregulate ACE2 possibly making unable the enzyme to exert protective effects in organs.…”
Section: Introductionmentioning
confidence: 99%
“…The aldosterone synthesis and secretion pathway were only shown in conjunction with ZT, but is related to renin secretion and adrenergic signaling in cardiomyocytes. A randomized, double-blind, placebo-controlled study showed that excess aldosterone secretion resulted in proarrhythmic effects and moreover confirmed that drugs affecting the renin-angiotensinaldosterone system (RAAS) were of benefit for arrhythmia and its comorbidities (56). A systematic review provided evidence that ACEI/ARB and aldosterone inhibitors could prevent the recurrence of AF (57).…”
Section: Shared Signaling Pathways Of Pharmacogeneticsmentioning
confidence: 92%